Integración de aplicaciones web y móvil, para la gestión de restaurantes y servicio al cliente. - Banda Bermeo, Jairo Israel (2016)
To achieve compliance with the strategic planning of the companies related to the restaurant industry, are required various activities, that facilitate customer service and management of business processes, it is there, where arise a variety of problems that, until now they have been treated on the fly using traditional methods to meet the management of the services that offer the same. The possibility of bringing a software solution that cooperates with the increase in business productivity of restaurants emerges, and to optimize and increase the effectiveness in carrying out its business processes customer service, by integrating web and mobile applications for restaurant management and customer service. The realization of this innovative approach involves enhancing the performance of activities in various areas, thereby, Loja will be inevitably intruded on economic growth, through its investors in the restaurant business, who will strengthen tourism and culture by presenting quality services and modern technology. It has improved the user-client interactivity and vice versa, allocation tables, orders, cancellation of orders among the most relevant. A set of methods was used, including scientific, inductive, deductive, hybrid method, and the following software tools: JSF, PrimeFaces, PrimeFaces Mobile, MySQL, Push Messages. The used techniques are: analysis of business processes, direct observation, direct information analysis, interviews, and surveys. This application is built on the ICONIX methodology that indicates its software development in the requirements analysis phase, analysis and preliminary design and design and implementation, resulting in an intuitive user-friendly application.